What do primary school students’ drawings tell us about their mental models on marine environments? - Atasoy, Volkan; Ahi, Berat; Balci, Sibel (Informa UK Limited, 2020)
The current study aims to investigate the mental models of primary school students about marine environments and how variables such as gender, grade level, and city of residence affect their mental...
Keywords: Education & Educational Research; 4. Education; 14. Life underwater